DEVELOPMENT AND CHARACTERIZATION OF PALONOSETRON HYDROCHLORIDE JELLIES - Islam, Md. Shahidul; Mojumder, Tanjum Jahan; Nawrin, Farjana (Universal Journal of Pharmaceutical Research, 2023)
Aim and objective: Dysphagia is one of the most common diseases mainly in geriatric and podiatric populations. As swallowing is the main difficulty in dysphagic patients, in that situation medicated jelly preparations are the best alternative to conventional doses forms (tablets and capsule doses form). This research article is aimed at the formulation and evaluation of Palonosetron hydrochloride oral jelly to avoid swallowing related issues in paediatric and geriatric patients and to improve its bioavailability. Methods: Two methods i.e., congealing and heating were chosen to prepare sucrose-based jellies. All prepared formulation were evaluated on different parameters like physical appearance, drug content, pH and dissolution study, stability study etc. Results: All formulation was found free from any type of gritty particles. Out of all formulations MJ1 was found best formulation on the basis of drug release profile i.e., 79.22% within 30 mins. Accelerated stability studies also confirmed that MJ1 and MJ2 are the best formulations. Conclusion: This study concludes that Palonosetron hydrochloride can be delivered successfully by the means of jellies to avoid first pass metabolism. Peer Review History: Received: 5 April 2023; Revised: 8 May; Accepted: 28 June 2023; Available online: 15 July 2023 Academic Editor: Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com Reviewers: Rola Jadallah, Arab American University, Palestine, rola@aauj.edu Dr. Ogbonna B. Onyebuchi, Nnamdi Azikiwe University, Awka, Nigeria, summitpharm@yahoo.com